From biophysics to cellular function: neural TELCs-membrane-anions capacitor transmembrane potential - Lee, James Weifu (Frontiers in Biophysics, 2025)
Based on the transmembrane-electrostatically localized protons/cations charges (TELCs) theory, neural transmembrane potential including both resting and action potential is now well elucidated as the voltage contributed by the TELCs-membrane-anions capacitor biophysics in a neuron. Accordingly, neural transmembrane potential has an inverse relationship with TELCs surface density, which may represent a substantial progress in bettering the fundamental understanding of neuroscience. In this article, I will present a review on the latest development of the TELCs neural transmembrane potential theory and address Silverstein’s interesting arguments regarding the TELCs model that may constitute a complementary development to both the Hodgkin-Huxley classic cable theory and the Goldman-Hodgkin-Katz equation. A series of predictions from the TELCs model regarding crucial ion channels have exactly been experimentally observed in many well-established electrophysiological phenomena including (but not limited to): 1) The tetrodotoxin (TTX) sensitivity shows the complete blockade of action potentials by TTX; 2) Genetic knockout or mutation of critical ion channels abolishes action potential spike; and 3) The precise clustering of ion channels at the axonal initial segment and nodes of Ranvier underlies the ability to fire action potential spikes and the saltatory conduction along a myelinated axon. This indicates that the TELCs model can be well predictive and provide new opportunities as a theoretical tool for further research to better understand neurosciences.